Empowerment of posyandu cadres in creating healthy villages free of stunting - Indarwati Indarwati; Tri Susilowati; Annisa Andriyani (Universitas Muhammadiyah Magelang, 2024)
The stunting rate in Kedungan Village remains unchanged, with 19 toddlers affected in 2023 and one reported death in 2024. The primary objective of the community service activities is to enhance the knowledge of posyandu cadres regarding stunting and its prevention, as well as to improve their skills in food preparation and presentation to support the nutritional resilience of stunted toddlers. These activities are conducted in stages, beginning with coordination, followed by socialization about stunting and its prevention, training on food processing and serving techniques, and mentoring cadres in providing supplementary feeding (PMT) to stunted toddlers. The outcomes of these activities demonstrated a significant increase in participants' knowledge about stunting and its prevention, with the average correct answers rising from 54.1% in the pre-test to 74.3% in the post-test. Regarding practical application, the processed PMT distributed at the posyandu has adhered to the techniques taught during the training, including proper food preparation and presentation. Meals were served in an appealing manner, following the examples provided during the training sessions.